Effect of medial opening wedge high tibial osteotomy on intraarticular knee and ankle contact pressures. Issue 4 (April 2015) - Suero, Eduardo M.; Sabbagh, Yaman; Westphal, Ralf; Hawi, Nael; Citak, Musa; Wahl, Friedrich M.; Krettek, Christian; Liodakis, Emmanouil
ABSTRACT: High tibial osteotomy (HTO) is a commonly used surgical technique for treating moderate osteoarthritis (OA) of the medial compartment of the knee by shifting the center of force towards the lateral compartment. Previous studies have documented the effects of HTO on the biomechanics of the knee. However, the effects of the procedure on the contact pressures within the ankle joint have not been as well described. Seven cadavers underwent an HTO procedure with sequential 5° valgus realignment of the leg up to 15° of correction. An axial force of up to 550 N was applied and the intraarticular pressure was recorded. Minor valgus realignment of the proximal tibia does not significantly alter the biomechanics of the ankle. However, moderate‐to‐large changes in proximal tibial alignment result in significantly decreased tibiotalar contact surface area and in changes in intraarticular ankle pressures. These findings are clinically relevant, as they provide a biomechanical rationale for the diagnosis and treatment of ankle symptoms in the setting of lower limb malalignment or after alignment correction procedures. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:598–604, 2015.